PENGUKURAN KINERJA BADAN AMIL ZAKAT DAERAH (BAZDA) KABUPATEN X DI WILAYAH EKS KARESIDENAN BANYUMAS DALAM PERSPEKTIF BALANCED SCORECARD - Puji Lestari (InFestasi, 2010)
The purpose of this research is to evaluate the performance of Tithe Board (BAZDA) with using Balanced Scorecard perspective. This research approach is qualitative research. The data is collected by interview, questionnaire and literature study.The result of research shows that employee and committee loyalty viewed from learning and growth perspective is good. Viewed from internal business process, BAZDA has to improve social activities to society, and viewed from costumer perspective, BAZDA has try to increase customer (muzakki) by sending appeal letter, and distributing 75% tithe to society. The BAZDA’s financial performance still has to improve because the financial distribution for ZIS is still low than financial receipt.This research has implication that BAZDA has to do strategic planning comprehensive and coherence wtih changing shorterm and longterm planning pola. The BAZDA management is necessary to promote social activities by electornic media and others so that the society is easy to get access. Thi is be able to get new costumer (muzakki).